Electrically conductive and superhydrophobic textiles via pyrrole polymerization and surface hydrophobization after alkaline hydrolysis. Issue 8 (April 2019) - Lee, Su Jin; Yun, Changsang; Park, Chung Hee
The objective of this study was to impart the electrical conductivity to the polyester fabric by applying polypyrrole having a good atmospheric stability, and to fabricate the superhydrophobic surface by using perfluorodecyltriethoxysilane to increase the durability and practicality of electrically conductive fabric. Nanoscale roughness that is essential for superhydrophobicity was given to polyester fabric by the alkaline hydrolysis. Samples simultaneously subjected to surface hydrophobization and the treatment for electrical conductivity exhibited the excellent electrical conductivity (0.55 kΩ/sq). However, in this case, static contact angle of the water droplet was 148.2°, and shedding angle was >10°, thus confirming that the superhydrophobic property was not exhibited. Samples subjected to surface hydrophobization after the treatment for electrical conductivity had an electrical conductivity and superhydrophobicity with an electrical surface resistivity of 0.87 kΩ/sq, water contact angle of 154.8°, and water shedding angle of 5.0°. This polyester fabric showed reasonable air permeability, water vapor transmission rate, and functional durability to various liquids. The developed fabric can be exposed to a reduced number of washing cycles due to its self-cleaning properties, thereby made able to exhibit a durable conductivity during its use phase.